Humoral Response to SARS-CoV-2 Vaccine-Boost in Cancer Patients: A Case Series from a Southern European Cancer Center - Júlio Oliveira; Pedro Cruz; Tânia R. Dias; Mário Sousa-Pimenta; Beatriz Almeida; Bruno Soares; Hugo Sousa; Rui Costa; Carlos Ochoa; Francisca Dias; Rui Medeiros (Vaccines)
Background: Cancer patients face a greater risk of complications and death after contracting the SARS-CoV-2 virus. Booster doses of the COVID-19 vaccine were suggested to provide additional protection. This study aimed to assess how cancer patients’ immune systems respond to the booster shots and categorize their responses. Methods: We analyzed 735 samples from 422 individuals, including patients followed at the Portuguese Oncology Institute of Porto (IPO-Porto). Three cohorts were recruited, and blood samples were collected 3- and 6-months post-booster dose: cohort 1 cancer patients (also collected before the booster); cohort 2 cancer patients; and cohort 3 (healthy individuals). Humoral immune response was evaluated by analyzing IgG levels against the SARS-CoV-2 Spike (S) protein. IgG levels against the SARS-CoV-2 Nucleocapsid(N) protein was also analyzed in order to address previous contact with the virus. Results: Among Cohort 1 patients with solid tumors, when compared to pre-boost, IgG S levels increased 3 months after the boost and remained high after 6 months. Patients with hematologic tumors demonstrated lower IgG S levels at both timepoints. Comparing the IgG S levels among hematological tumors, solid tumors, and healthy individuals in both timepoints we observed that the healthy individuals had the strongest IgG S response, followed by the solid, and, lastly, the hematologic tumors. Solid tumor patients undergoing chemotherapy had reduced IgG S levels, especially those on high febrile neutropenia risk regimens. Conclusions: In conclusion, cancer patients have a weaker immune response to the SARS-CoV-2 vaccine, especially those with hematological cancers. Chemotherapy and febrile neutropenia risk further reduce booster effectiveness. Further research is needed to optimize vaccine timing for cancer patients undergoing chemotherapy.